HUBUNGAN TRAINING, MOTIVASI KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PERAWAT PADA RSUD DR. ADNAAN WD PAYAKUMBUH - Bismar Raja (Al Dzahab: Journal of Economics, Management, Business and Accounting, 2023)
Purpose: This study aims to determine training, work motivation and organizational commitment to the performance of nurses at RSUD Dr. Adnaan Wd Payakumbuh Design/methodology/approach: . The method used  multiple linear regression analysis Findings: that there is a positive and significant effect of training on the performance of nurses where t-count is greater than t-table (8,108> 2,010) or the level is significantly less than alpha (0.000 < 0.05). There is a positive and significant effect of work motivation on the performance of nurses where t-count is greater than t-table (2.205> 2.010) or the level is significantly smaller than alpha (0.032 <0.05). There is a positive and significant effect of organizational commitment on nurse performance where t-count is greater than t-table (3.580>2.010) or significantly lower than alpha (0.001 <0.05). The F test has the effect of training, work motivation and organizational commitment together and has a positive and significant effect on the performance of nurses where the f-count is greater than the f-table value (58.706>2.73) with a significant level of 0.000 less than 0.05 . Where the value that has the most dominant influence on the performance of nurses is the training variable. The contribution of training variables, work motivation and organizational commitment is 0.756 or 75.6% while the remaining 24.4% is influenced by other variables. Research implications: the authors suggest to RSUD Dr. Adnaan Wd Payakumbu to further improve training because it has the greatest influence on the performance of nurses.